Laplacians on quantum hypergraphs. Issue 1 (December 2014) - Mugnolo, Delio
Abstract We introduce quantum hypergraphs, in analogy with the theory of quantum graphs developed over the last 15 years by many authors. We emphasize some problems that arise when one tries to define a Laplacian on a hypergraph. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)